Effects of hydrogen implantation on the magnetocaloric properties of amorphous FeZr films. (April 2021) - Alouhmy, M.; Moubah, R.; Alouhmy, G.; Abid, M.; Lassri, H.
Abstract: We report on the effects of H-implantation on the magnetic and magnetocaloric properties of amorphous FeZr films. Arrott plots reveal a second order ferromagnetic to paramagnetic phase transition for the as-grown and H-implanted films, with an increase in TC from 160 to 200 K upon implantation. The maximum change in magnetic entropy (- Δ S M ) increases from 0.66 to 0.77J/kgK for a field change μ0 ΔH = 1.5T, as well as the relative cooling power (RCP) values were improved from 84.5 to 108.6J/kg. This improvement was attributed to the increase in magnetization and chemical inhomogeneity induced by the implantation process. The increase in the chemical inhomogeneity was supported by the determination of the local exponent n extracted from the slope of Ln(− Δ S M ) as a function of Ln( μ 0 H ), which is line with the simulated depth profile of hydrogen atoms through the FeZr film. Highlights: The effects of H-implantation on the magnetic and magnetocaloric properties of Fe93 Zr7 were investigated. Upon H-implantation, both the magnetization and TC increase. The maximum change in magnetic entropy as well as the relative cooling power were improved upon H-implantation. The chemical inhomogeneity induced by the implantation process leads to a significant increase in the magnetocaloric performance.